Bovine Hydatid Cyst: Prevalence, Characterization, Public Health and Economic Importance at adama Abattoir, Central Ethiopia - Tesfaye Belachew; Mekdes Abay; Teshome Gunse (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
A purposive study was conducted from November 2011 to April 2012 with the objective of determining the characteristics of hydatid cysts and to assess the current status of economic losses of hydatidosis in cattle slaughtered at Adama municipality abattoir. Hydatid cysts were characterized on the basis of their size, fertility and viability. Routine meat inspection procedure was conducted on organs namely lung, liver, kidney, heart and spleen involving visualization and palpation to detect the presence of hydatid cysts. Out of the total of 2276 hydatid cysts counted, 1126(49.5%), 913(40.1%) and 237(10.4%) were found to be small, medium and large size respectively. Out of the total of 300 cysts examined for the fertility test, 29(9.6%), 188(62.6%) and 83(27.6%) were found to be fertile, sterile and calcified respectively. The rate of cyst calcification was higher in the liver than in the lung while fertility rate was higher among the cysts of the lung. The direct financial loss during the study period was 8,749 ETB. This result was assessed from the mean retail market price of each organs multiplied by the total number of organs condemned at Adama abattoir during the study period.